Behavioristic Approach Strategy Fostering a Spirit of Nationalism in the Elementary School Teacher Education Study Program - Dahnial, Irfan; Wanda, Karina; Sagala, Rakhmat Wahyudin (University of Muhammadiyah Malang, 2024)
The research aimed to explore and analyze strategies for fostering nationalistic attitudes in students of the Primary School Teacher Education Study Program through a Behavioristic approach to learning Citizenship Education. The research method employed descriptive qualitative research with the aim of finding out behavioristic strategies for fostering a nationalistic attitude and how to foster a nationalistic attitude through a behavioristic approach. Techniques for collecting data through interviews and document analysis are related to the use of a Behavioristic approach in learning Citizenship Education. The findings indicated that an effective strategy for fostering nationalistic attitudes in students in the Primary School Teacher Education Study Program is through a Behavioristic approach. First, the use of positive reinforcement is an effective strategy for strengthening nationalist attitudes. In the learning context, positive reinforcement can be provided through recognition and appreciation for students' active participation in activities related to citizenship, such as flag ceremonies, national day commemorations, or citizenship projects. Second, learning that involves direct experience and practical application has also proven effective in fostering nationalistic attitudes. By presenting real situations that are relevant to national values, such as visits to historical places or participation in social activities related to society, students can directly experience nationalist values and internalize them. The implications of this research can be used as a guide for lecturers and instructors in designing learning strategies that can strengthen students' nationalist attitudes.